Atypical cerebral and cerebellar language organisation: a case study. Issue 1 (December 2015) - van Dun, Kim; De Witte, Elke; Van Daele, Wendy; Van Hecke, Wim; Manto, Mario; Mariën, Peter
Abstract Background In the majority of right-handed subjects, language processing is subserved by a close interplay between the left cerebral hemisphere and right cerebellum. Within this network, the dominant fronto-insular region and the contralateral posterior cerebellum are crucially implicated in oral language production. Case Presentation We report atypical anatomoclinical findings in a right-handed patient with an extensive right cerebellar infarction and an older left fronto-insular stroke. Standardised neurolinguistic and neurocognitive test batteries were performed. In addition, fMRI, DTI, and SPECT results are reported. In this patient, disruption of the cerebellocerebral language network due to vascular damage in the left fronto-insular region and right posterior inferior cerebellar artery (PICA) territory did not induce any speech or language deficits. By contrast, executive and behavioural disturbances were found after the right cerebellar stroke. Evidence from fMRI and DTI suggests atypical bilateral language representation (Laterality Index = +0, 11). At the cerebellar level, fMRI showed more activated voxels in the left than in the right hemisphere (Laterality Index = +0, 66). Conclusion We hypothesise congenital bilateral language representation in this patient which might be more advantageous than a typically lateralised distribution of linguistic functions to compensate acute damage to critical language regions. The more activated left cerebellum possibly compensated the functional loss in the right cerebellum after acute damage due to bilateral organisation of language function. However, more research is needed to confirm this hypothesis.